1997
DOI: 10.1111/j.1365-2915.1997.tb00420.x
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal prevalence of ticks and tick‐transmitted haemoparasites in traditionally managed N'Dama cattle with reference to strategic tick control in the Gambia

Abstract: A survey of tick spatial and seasonal distribution in traditional managed N'Dama cattle over 1 year old was carried out in The Gambia over 16 months. Presence of Anaplasma marginale and Babesia spp. in the blood smears and their antibodies in the serum of same animals were also examined. Tick species, in decreasing order of abundance, were: Boophilus geigy, Rhipicephalus senegalensis, B.decoloratus, Hyalaomma truncatum, H.marginatum rufipes and Amblyomma variegatum. All tick species peaked during the rainy sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 13 publications
2
18
0
Order By: Relevance
“…Prevalence of blood protozoan diseases was higher in rainy season (45.45%) than that in the summer (27.87%) and winter (16.55%) ( Table 3). This finding was similar to the study of Perez et al (1994) and Mattioli et al (1997) who recorded that rainy season is the most important factor in the prevalence of anaplasmosis and babesiosis. It is assumed that, due to the availability of green grasses in the rainy season, the animal maintain a good health and remain carrier state in endemic areas.…”
Section: Resultssupporting
confidence: 80%
“…Prevalence of blood protozoan diseases was higher in rainy season (45.45%) than that in the summer (27.87%) and winter (16.55%) ( Table 3). This finding was similar to the study of Perez et al (1994) and Mattioli et al (1997) who recorded that rainy season is the most important factor in the prevalence of anaplasmosis and babesiosis. It is assumed that, due to the availability of green grasses in the rainy season, the animal maintain a good health and remain carrier state in endemic areas.…”
Section: Resultssupporting
confidence: 80%
“…They recorded highest counts of A. variegatum in July and April, which coincide with the rainy months for the areas. Moreover, Hoogstraal (1956), Morel (1980), Petney et al (1987), Yohualashet et al (1995), Mattioli et al (1997), Bekele (2002) and Assefa (2004) observed the seasonal fluctuation of this tick species with a relative rise in numbers during the short and long rains. The life-cycle of this tick species is most closely linked to rainfall.…”
Section: Discussionmentioning
confidence: 99%
“…The traditional management system of small ruminants in The Gambia substantially diminishes the likelihood of tick infestation of neonates at or immediately after birth. Parturitions at Keneba and Kerr Seringe occurred in pens, which were regularly cleaned; and at Keneba all births happened precisely between 11 March and 8 April, coinciding with the period of significant decline in Amblyomma nymphs (or near complete disappearance) and least activity of Amblyomma ticks [27]. Furthermore, the period required for transmission of E. ruminantium to occur after attachment of an infected tick to a susceptible host is estimated between 27 and 38 hours for nymphs and between 51 and 75 hours for adults [41], and it is highly unlikely that E. ruminantium transmitted to neonates at birth through tick bite could appear in the blood stream on the very day of or the following day after birth and detected by PCR.…”
Section: Discussionmentioning
confidence: 99%
“…At the study sites, peak activity of Amblyomma nymphs occurs from November to January, which is followed by rapid decline or virtual disappearance of the tick population (both nymphs and adults) until May/June when adult ticks start to appear on animals [27], most frequently on cattle. Whole blood was collected with and without anticoagulant (EDTA) from each newborn animal on the day of birth or at the latest within 3–10 days of birth, and thereafter weekly and fortnightly for testing by pCS20 PCR and MAP1-B ELISA respectively.…”
Section: Methodsmentioning
confidence: 99%